ELECTRIC AND MAGNETIC FIELDS GENERATED BY ELECTROKINETIC PROCESSES IN A CONDUCTIVE CRUST - Fedorov E.; Pilipenko V.; Uyeda S. (My University, 2001)
The results of different models of electrokinetic sources of ULF disturbances, mostly based on numerical calculations, can be reproduced with a much simpler analytical model of an elliptic-shaped inhomogeneity. The suggested model can be applied to the estimates of electromagnetic fields from elementary sources of different geometries. Moreover, this model enables one to estimate the screening effect of the back conductivity currents and the influence of the ground-atmosphere boundary. The estimates show that the expected magnitudes of seismo-electromagnetic signals in ULF band from an elementary electrokinetic source may reach the detection level only for rather favorable set of crustal parameters.